(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Retroperitoneal hematomas during pregnancy arising from ovarian vessels are rare. This condition is usually associated with hemorrhagic shock and can lead to serious maternal-fetal morbidity or mortality. Carrying a pregnancy to term when the condition is diagnosed in early pregnancy is therefore not guaranteed. Case presentation: A 39-year-old para 4+1 presented at 26 weeks of gestation with a 2-day history of right lower abdominal pain after a fall on her farm two weeks before admission. She was anemic, and abdominal ultrasound revealed a hypoechoic mass in the right lower quadrant of the abdomen, which, upon explorative laparotomy, turned out to be a large nonexpanding zone III retroperitoneal hematoma. Conservative management without opening the hematoma was performed, and she was serially imaged to assess the etiology and to rule out any further bleeding. The patient carried the pregnancy to term and delivered vaginally. Postpartum exploration of the abdomen during tubal ligation revealed resolution of the hematoma. Discussion: Retroperitoneal hematomas can occur spontaneously or can be caused by blunt or penetrating trauma. Patients mostly present with abdominal pain, hypovolemia, or anemia. For descriptive purposes, the retroperitoneum is divided into three zones: central, perirenal, and pelvic. For spontaneous or blunt trauma hematomas in the pelvic zone, conservative management without opening the hematoma is advised. Conclusion: Retroperitoneal hematoma should be a differential diagnosis in a patient presenting with an acute abdomen during pregnancy. Although associated with morbidity and mortality during pregnancy, patients with this condition can still carry their pregnancy to term and deliver normally.